1996
DOI: 10.1007/bf01487749
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans induces the release of inflammatory mediators from human peripheral blood monocytes

Abstract: Candida albicans (C. albicans) is a major nosocomial pathogen. We examined arachidonic acid (AA) and cytokine production by monocytes stimulated with C. albicans. [14C]-AA labeled monocytes released 8.9 +/- 2.3% of the incorporated AA following stimulation with live C. albicans (C. albicans: monocyte of 16:1) (P = 0.0002). Prior studies indicate that soluble alpha-mannans and beta-glucans antagonize mannose and beta-glucan receptors, respectively. Preincubation of monocytes with alpha-mannan (100 micrograms/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 45 publications
1
21
0
1
Order By: Relevance
“…These findings agree with earlier reports (3,6,10,18). Production of these cytokines under the influence of C. albicans may enhance acute inflammatory cell influx into infected tissues, activate leukocytes, and promote early noncognate elimination of the organism prior to the development and/or mobilization of an adaptive specific immune response (30,38).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These findings agree with earlier reports (3,6,10,18). Production of these cytokines under the influence of C. albicans may enhance acute inflammatory cell influx into infected tissues, activate leukocytes, and promote early noncognate elimination of the organism prior to the development and/or mobilization of an adaptive specific immune response (30,38).…”
Section: Discussionsupporting
confidence: 94%
“…Monocytes have the capacity to produce chemokines (23), proinflammatory cytokines (6), and particularly the immunoregulatory cytokines interleukin-10 (IL-10) and IL-12 (9,41). Immunoregulatory cytokines released as a result of the initial contact of Candida with host monocytes/macrophages can also be a major factor, which can potentially regulate the acquired immune response through T-cell development, in host defense.…”
mentioning
confidence: 99%
“…Possible candidates to mediate this defect could be pattern recognition receptors (21), such as the mannose receptor (29), the ␀ glucan receptor (11), or the Toll-like receptors (15), as they could confer the specificity of the defect to Candida and are also directly involved in the regulation and direction of cytokine production patterns (21). It has been shown that binding of Candida mannan to normal monocytes/macrophages directly stimulates TNF-␣ production by mouse alveolar macrophages (10), while binding of Candida via the mannose and ␀-glucan receptor stimulates the release of inflammatory eicosanoids from human peripheral blood monocytes (4). Human monocytes stimulated with Candida produce IL-1␀, IL-6, and IL-8 (9), while it was recently shown that activation of human Toll-like receptors induces production of IL-1, IL-6, and IL-8 (22), as well as other cytokines (30).…”
Section: Discussionmentioning
confidence: 99%
“…12 Superantigens Huang et al, 1997a;Huang et al, 1997b;Roggiani et al, 1997 Exotoxins Hackett andStevens, 1992;Fitzgerald and Pastan, 1993;Bhakdi et al, 1994;Houldsworth et al, 1994;Murai et al, 1996 Lipoarabinomannans (from mycobacteria) Carson et al, 1988;Rawadi and Roman-Roman, 1996 Fungal components (e.g., mannans, glucans, mannoproteins) Barwick et al, 1994;Castro et al, 1996 Parasite components (e.g., phosphoinositol) Bate et al, 1989 Viruses Barry et al, 1976;Jakeman et al, 1991;Gong et al, 1991;Becker et al, 1991;Alluwaimi et al, 1994;Chang and Shaio, 1994;Kurokawa et al, 1996;Price et al, 1997 Non-microbiological contaminations (e.g., cytokines, media, Soprana et al, 1994 cells, breakdown products) Solid materials (e.g., medical devices, plastic) Miller and Anderson, 1988 Drugs (e.g., steroids, bile salts, dapsone, cytokines) Beloeil et al, 1980;Bodel and Dillard, 1968;Coleman, 1995 and lipoproteins are all potent cytokine inducers that were able to fulfill at least three of Koch and Dale's criteria to prove their role as cytokine inducers in human cells. the presence of lPS was mostly excluded by the lAl assay.…”
Section: Substances Referencesmentioning
confidence: 99%